THE SCOPE OF THE APPLICATION OF THE EUROPEAN UNION COMPETITION LAW TO PUBLIC HEALTHCARE SERVICES - Janeckaitė, Rūta (Teisė, 2017)
The article examines the extent to which European Union competition law is applicable to public healthcare services. For this purpose, the article analyses the notion of company within the meaning of competition law and aims to establish how this notion could be applied to public healthcare services. It furthermore considers the application to public healthcare of Articles 106 and 107-109 of the Treaty on the Functioning of the European Union (TFEU) establishing derogations from EU competition rules. The article compares the extent of the application of the competition law to public healthcare with that one of the internal market freedoms. The analysis and the conclusions in the article are based on the EU legal acts, documents of the European Commission and cases in the area of public services and competition law decided by the Court of Justice of the EU and the General Court.